Uncovering the groundwater resource potential of Murchison Region in Western Australia through targeted application of airborne electromagnetics. Issue 1 (1st December 2016) - Davis, Aaron; Shudra, John; Macaulay, Scott; Munday, Tim; Ibrahimi, Tania; Sorensen, Camilla
Abstract : Access to water is identified a key infrastructure need for mining, energy and industry development. In Western Australia, the scale of planned developments linked to current mineral exploration and mining is set to generate significant economic value for the State, but its realisation is dependent on ensuring access to groundwater. To address these issues, The WA Government Department of Water (DoW) has embarked on a series of groundwater investigations to identify and establish long-term water resources in regional areas where agriculture and mining opportunities have the potential for development. The Murchison in northern WA was identified as one of six key priority areas for this initiative. With numerous known mineral deposits having potential for development, locating and securing an adequate, sustainable long-term water supply is a critical consideration if these mineral resources are to be developed further. While it is known that there are significant groundwater resources in the region, at present these are generally poorly understood. Of particular importance are the palaeovalley aquifers which are known (locally) to contain a significant resource, but which are relatively poorly characterised. To aid an understanding of their extent an airborne electromagnetic (AEM) survey was commissioned and flown in the Murchison extending over an area in excess of ~ 106 000 km 2 . Prior studies at a local scale had indicated that airborne EM would be very effective at defining the location and thickness of palaeovalleys in the region. Pilot investigations also determined the most appropriate AEM system to use for acquisition. These studies suggested that the buried palaeovalleys were most likely to be near-coincident with contemporary valley systems developed in a granite/gneiss-greenstone basement. Covering such a large region required a novel approach to survey design to maximize the information relating to their expected spatial variability. Therefore a terrain index (MrVBF) was used with the SRTM 1sec DEM to define the extent of contemporary valleys, and the extent of the AEM survey area. This approach allowed survey acquisition costs to be kept to less than half that of flying a more "traditional" survey over the entire area. It also allowed for the acquisition of data with a closer line spacing than would have been possible otherwise, therefore capturing more of the spatial variability associated with the palaeovalley systems. The results have demonstrated the validity of the strategy adopted and have shown that in the absence of conventional hydrogeological information, geophysical methods are demonstrably a cost and time effective approach to upscaling local hydrogeological information, thereby fast tracking groundwater resource assessments that would otherwise take decades to complete.